Encountering Jesus in the real world of the Gospels - Parker, Cyndi (Hendrickson Publishers, Peabody, Massachusetts, 2021)
"This book focuses on the complexities of the political, social, literary, and religious context of the Gospels. The purpose is to advance readers' understanding of the Gospels and help them encounter Jesus, the disciples, and crowds as real people in a real place at a time vastly different from today"--
Eden to exile Land of the gospels International drama Geography and politics Lifelong learning Birth narrative Entering ministry A skilled communicator - Passion Week From death to new life
Keywords: Christian Bible History & Culture